Fasttrack : managing symptoms in the pharmacy - Nathan, Alan (London ; Chicago : Pharmaceutical Press, 2012)
Contains all the essential information required for managing symptoms presented in the pharmacy, and covers the common ailments that pharmacists are likely to be presented with.
Keywords: Pharmacists; Pharmaceutical Services; Diagnosis; Diagnosis; Pharmaceutical services; Pharmacists; Pharmaceutical Services